2010
DOI: 10.1021/nn901824n
|View full text |Cite
|
Sign up to set email alerts
|

Structural-Mechanical Characterization of Nanoparticle Exosomes in Human Saliva, Using Correlative AFM, FESEM, and Force Spectroscopy

Abstract: All living systems contain naturally occurring nanoparticles with unique structural, biochemical and mechanical characteristics. Specifically, human saliva exosomes secreted by normal cells into saliva via exocytosis, are novel biomarkers showing tumor-antigen enrichment during oral cancer. Here we show the substructure of single human saliva exosomes, using a new ultra sensitive low force Atomic Force Microscopy (AFM) exhibiting sub-structural organization unresolvable in Electron Microscopy. We correlate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
289
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 330 publications
(306 citation statements)
references
References 27 publications
15
289
2
Order By: Relevance
“…Currently, the cup shape of exosomes identified through negative staining has been considered to be their typical structure (Gyorgy et al, 2011;Thery et al, 2009). However, scanning EM (SEM) (Enderle et al, 2015), atomic force microscopy (Sharma et al, 2010), and cryo-transmission EM (TEM) (Montaner-Tarbes et al, 2016;Saari et al, 2015) revealed that exosomes have a round shape. In this study, we investigated the structure of exosomes using various EM approaches, including block preparation, sectioning, focused ion beam (FIB)-SEM, electron tomography, and cryo-TEM.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the cup shape of exosomes identified through negative staining has been considered to be their typical structure (Gyorgy et al, 2011;Thery et al, 2009). However, scanning EM (SEM) (Enderle et al, 2015), atomic force microscopy (Sharma et al, 2010), and cryo-transmission EM (TEM) (Montaner-Tarbes et al, 2016;Saari et al, 2015) revealed that exosomes have a round shape. In this study, we investigated the structure of exosomes using various EM approaches, including block preparation, sectioning, focused ion beam (FIB)-SEM, electron tomography, and cryo-TEM.…”
Section: Introductionmentioning
confidence: 99%
“…Cryo-electron tomography microscopy was shown to be useful to avoid such types of artifacts [20,21]. Also, scanning electron microscopy [22], single particle electron microscopy [23], and atomic force microscopy were used successfully to visualize individual EVs [13,22]. Further non-conventional techniques of analysis (suitable for the analysis of EVs and liposomes) include dynamic light scattering analysis (DLS), nanoparticle tracking analysis (NTA) [24,25], and fl uorescence nanoparticle tracking analysis (F-NTA) [26], Raman spectroscopy-based techniques, stimulated emission depletion (STED) microscopy, impedance-based fl ow cytometry, and resistive pulse sensing [27].…”
Section: Detection Methods Of Evsmentioning
confidence: 99%
“…To this end, all tissues embed population(s) of resident stem cells that live and grow as pericytes [1] in a perivascular location within a complex environment named "the niche", entailing both chemical (trophic mediators) and physical cues [2]. A consistent amount of signaling peptides in the extracellular space are not naked molecules, but rather reside together with miRNA, long-chain RNA, and other molecules inside exosomes [3]. These are nanovescicles interconnected by a network of filaments whose effective nature still remains elusive, and can be viewed as timely delivery machines of pockets of information [3,4].…”
Section: S2mentioning
confidence: 99%
“…A consistent amount of signaling peptides in the extracellular space are not naked molecules, but rather reside together with miRNA, long-chain RNA, and other molecules inside exosomes [3]. These are nanovescicles interconnected by a network of filaments whose effective nature still remains elusive, and can be viewed as timely delivery machines of pockets of information [3,4]. Our view of cell-to-cell connectedness is currently evolving accordingly.…”
Section: S2mentioning
confidence: 99%